Pengaruh Latihan Kekuatan Otot Lengan Dan Bahu Terhadap Hasil Tolak Peluru Siswa Kelas VIII SMP Negeri 2 Rokan IV Kabupaten Rokan Hulu - Hendri Mulyadi; Debby Indah (STKIP ROKANIA, 2018)
This research, spesifically, an experiment that delivering the practice of arm muscle strength and shoulder to increase the result. This research was conducted at SMP Negeri 2 Rokan IV Koto Kab. Rokan Hulu. The clasification result of samples, it was obtained 15 samples. This research used the models of total random sampling.The instrument of research used a test of weight throw and data with using t-test formula manually. The result shows an average of pre-test is 5.78. meanwhile, average of post-test is 6.30. with 5.740 t count and 1.761 for t table. This research indicates that the practice of arm muscle strength and sholuder could increase weight throw result.